Effect of Heat Radiation on Work Load and Gamelan Crafts Productivity - I Ketut Gede Juli Suarbawa; M. Yusuf (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
The production process of making gamelan in Tihingan Village still uses the traditional way, namely using prapen with an open flame both for the melting process and in the formation process. This causes the workload of craftsmen to be quite heavy due to exposure to radiant heat and dust. The results of microclimate measurement of the work environment obtained an average dry temperature of 33.2oC, an average wet temperature of 24oC. The average ball temperature was 33oC, WBGT 26.3oC and the mean humidity (RH) was 59.0%. The average light intensity at work reaches 319.2 lux. The average temperature of the furnace at low heat is 340oC and during the combustion process it reaches 860 oC. The results of measurements of air quality in the workplace include levels of NO2 17.00 µg /m3 (increased by 112.50%), SO2 5.33 µg/m3 (increased by 45.23%), CO 407.16 µg/m3 (increased by 217, 99%), oxidants (Ox) 61.00 µg/m3 (increased by 1.67%) and dust 48.50 µg/m3 (increased by 125.58%). The mean pulse of the nguwad workers reached 125.81±1.35 beats/minutes (including heavy workload). This causes the productivity of craftsmen to be low due to the increase in musculoskeletal disorders and craftsmen fatigue. To overcome this condition, the workings of the craftsmen need to be improved immediately through the application of appropriate technology in the form of furnace repair so that the flames and dust produced can be removed from the workplace, then exposure to hot air and combustion dust will no longer expose the craftsmen.